ANALISIS PENYELESAIAN TINDAK LANJUT HASIL PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN NGANJUK - , (Bilancia : Jurnal Ilmiah Akuntansi, 2022)
ABSTRACT The research aims to explain the mechanism for completing the follow-up results of the examination of the financial statements of the Nganjuk Regency Regional Government. The analysis used includes Planning, Organizing, Actuating, Controlling (POAC). The focus of this research is how the Nganjuk Regency Regional Government as an auditee in completing the follow-up of the examination results. This research is qualitative research with a case study approach. The informants in this study are the Head of the Nganjuk Regency Financial and Asset Management Agency, the Head of Accounting and Reporting, the Head of Reporting Subsection and Technical Staff for Accounting and Reporting which can be said to be a representative of the Nganjuk Regency Regional Government and most often communicates with the Financial Audit Board (BPK). The results of this study show that the completion rate of follow-up examination results in Nganjuk Regency has not been 100% resolved. The factors that become obstacles in the completion of the follow-up of the examination results are the absence of special policies that regulate the completion of follow-up examination results, coordination with regional device organizations (OPD) is not optimal, lack of commitment and motivation from the leadership. Keywords: follow-up; examination result; financial statements   ABSTRAK Penelitian bertujuan menjelaskan mekanisme penyelesaian tindak lanjut hasil pemeriksaan laporan keuangan Pemerintah Daerah Kabupaten Nganjuk. Analisis yang digunakan meliputi Planning, Organizing, Actuating, Controlling (POAC). Fokus penelitian ini adalah bagaimana Pemerintah Daerah Kabupaten Nganjuk sebagai auditee dalam menyelesaikan tindak lanjut hasil pemeriksaan. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Informan dalam penelitian ini adalah Kepala Badan Pengelola Keuangan dan Aset Daerah Kabupaten Nganjuk, Kepala Bidang Akuntansi dan Pelaporan, Kepala Sub-bagian Pelaporan dan Staf Teknis Bidang Akuntansi dan Pelaporan yang mana dapat dikatakan sebagai representatif dari Pemerintah Daerah Kabupaten Nganjuk dan paling sering berkomunikasi dengan Badan Pemeriksa Keuangan (BPK). Hasil penelitian ini menunjukkan bahwa tingkat penyelesaian tindak lanjut hasil pemeriksaan di Kabupaten Nganjuk belum 100% terselesaikan, adapun faktor yang menjadi penghambat dalam terselesaikannya tindak lanjut hasil pemeriksaan adalah belum adanya kebijakan khusus yang mengatur penyelesaian tindak lanjut hasil pemeriksaan, koordinasi dengan Organisasi Perangkat Daerah (OPD) tidak maksimal, kurangnya komitmen dan motivasi dari pimpinan. Kata kunci: tindak lanjut; hasil pemeriksaan; laporan keuangan